Laser wobble welding of fluid-based cooling channel joining for battery thermal management. (July 2021) - Kumar, Nikhil; Das, Abhishek; Dale, Tom; Masters, Iain
Graphical abstract: Highlights: Electric vehicle battery pack needs efficient joining method for thermal management. Laser welding of cooling channel to manifold was reported for the first time. Metallurgical and mechanical analyses confirmed suitability of laser welding. Modified throat thickness, a new response, was highly correlated with tensile load. A leak-proof cooling channel and module manifold joint was successfully produced. Abstract: Aluminium alloys are increasingly used to fabricate cooling channels for the thermal management of Li-ion batteries. Cooling channel fabrication involves a number of manufacturing operations including material extrusion, forming and joining/welding. In general, welding of aluminium alloys is challenging as they are both highly reflective and thermally conductive. To address the joining challenges, this paper is focused on developing an optimised joining process to connect a thin, flanged cooling channel to the thick module manifold of the battery thermal management system to create a watertight joint with high mechanical strength. As continuous seam welding was required, laser welding was the preferred as it is a non-contact process combining high speed and precision. For this application, 0.4 mm Al cooling channel was welded with 1.5 mm Al endplate/module manifold using a wobble head integrated with 1 kW CW fibre laser system. The effect of process parameters including line energy, incident angle, laser power, welding speed and beam offset were investigated to optimise both the weld geometry and strength. Microstructure, micro-hardness and grain formation analyses were carried out to understand the metallurgical behaviour of the weld. Beam offset had the most significant effect on the responses such as weld strength, throat thickness and modified throat thickness, and laser power had a significant influence on two key geometric features of the fusion zone, i.e. penetration depth and weld width. Weld strength was optimised using a developed surrogate model and a maximum load of 646.89 N was achieved using 0.2 mm beam offset, 331.82 W laser power and 659.10 mm/min welding speed. Using this optimum combination, a leak-proof cooling channel and module manifold joint were produced for battery thermal management.